The effect of polyphenol-rich dark chocolate on serum lipids in healthy subjects - Küçükyilmaz, Kübra; Okburan, Gözde; Gezer, Ceren (Revista de nutrição, 2024)
ABSTRACT Objective The present study aims to investigate the effects of consuming dark chocolate on the serum lipid profile of healthy adults. Methods The study was conducted over 4 weeks with a total of 37 subjects, including control (n=20) and intervention (n=17) groups. While the intervention group consumed 36g/day of dark chocolate (400 mg flavanol/day), the control group received no intervention. At the beginning and end of the study, some anthropometric measurements, blood pressure and biochemical parameters (low-density lipoprotein, high-density lipoprotein and total cholesterol, triglycerides, haemoglobin A1c and C-reactive protein, fasting blood glucose) were measured and 3-day food and physical activity records were taken every 15 days during the study period. Results After four weeks, body weight and body mass index decreased in the intervention group (p0.05). Low-density lipoprotein and total cholesterol also decreased in the intervention group (-8.16mg/dl and -10mg/dl, respectively; p0.05), and no change was observed in high-density lipoprotein cholesterol (p0.05). While an increase in fasting blood glucose was observed (p0.05), there was no difference in hemoglobin A1c and C-reactive protein levels (p0.05). Similarly, there was no change in systolic or diastolic blood pressure in either group (No-BreakpNo-Break0.05). Conclusion In conclusion, the consumption of 36g/day (400mg/day flavanol) for 4 weeks in healthy individuals can reduce low-density lipoprotein and total cholesterol without causing weight gain. Thus, cocoa consumption as a dietary intervention has a possible role in reducing the risk of cardiovascular disease as an age-related lifestyle disease. Long-term studies with larger samples are needed. RESUMO Objetivo O presente estudo tem como objetivo examinar os efeitos do consumo de chocolate amargo no perfil lipídico sérico de indivíduos adultos saudáveis. Métodos O estudo foi realizado com 37 indivíduos no total, incluindo os grupos controle (n=20) e intervenção (n=17), por 4 semanas. Enquanto o grupo de intervenção consumiu 36g/dia de chocolate amargo (400mg de flavanol/dia), o grupo controle não recebeu nenhuma intervenção. No início e no final do estudo, algumas medidas antropométricas, pressão arterial e parâmetros bioquímicos do sangue (lipoproteína de baixa densidade, lipoproteína de alta densidade e colesterol total, triglicerídeos, hemoglobina A1c (HbA1c) e C- proteína reativa, glicemia de jejum) foram medidos, e durante o período de estudo o consumo alimentar de 3 dias e os registros de atividade física foram feitos a cada 15 dias. Resultados Ao final de quatro semanas, os níveis de peso corporal e índice de massa corporal do grupo de intervenção diminuíram (p0,05). Além disso, LDL e colesterol total diminuíram no grupo de intervenção (respectivamente; -8,16mg/dl, -10mg/dl; p0,05) e nenhuma alteração determinada no colesterol HDL (p0,05). Enquanto um aumento é observado na glicemia evidente (p0,05), não há diferença nos níveis de HbA1c e PCR (p0,05). Da mesma forma, nenhuma alteração foi encontrada na pressão arterial sistólica e diastólica em ambos os grupos (p0,05). Conclusão Concluiu-se que, o consumo de 36g/dia (400mg/dia de flavanol) por 4 semanas em indivíduos saudáveis pode reduzir o LDL e o colesterol total sem causar ganho de peso. Assim, o consumo de cacau como uma intervenção dietética tem um possível papel para diminuir o risco de doença cardiovascular como uma doença relacionada ao estilo de vida relacionada à idade. Estudos de longo prazo com amostras maiores são necessários.